A global lesson : success through cooperation and compassionate leadership - Mohn, Reinhard, 1921-2009 (New York : Crown Publishers, 2009)
A legendary entrepreneur and father of the global media giant Bertelsmann offers penetrating insights into his motives, beliefs, and hopes as one of the world's foremost businesspeople.
Includes bibliographical references (p. [181]-185) and index.
Keywords: Mohn, Reinhard, -- 1921-2009.; C. Bertelsmann Verlag; Businessmen -- Germany -- Biography; Social responsibility of business; Entrepreneurship -- Social aspects; Industries -- Social aspects